2019
DOI: 10.1101/548446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic parallelism: concordance of patterns in closely related species illuminates underlying mechanisms in the historically glaciated Tasmanian landscape

Abstract: AbstractPhylogeography provides a means to understand mechanisms that shaped the distribution and abundance of species, including the role of past climate change. While concordant phylogeographic relationships across diverse taxa suggest shared underlying mechanisms (“phylogeographic parallelism”), it is also possible that similar patterns are the product of different mechanisms (“phylogeographic convergence”), reflecting variation among taxa in factors such as environmental to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Likewise, in the Southern Hemisphere (e.g. Tasmania, South Island of New Zealand), some species similarly appear to retreat from glaciated areas to refugial zones (Dussex, Wegmann, & Robertson, 2014; Kreger, Shaban, Wapstra, & Burridge, 2020; Leschen, Buckley, Harman, & Shulmeister, 2008; McCulloch et al., 2010; McKinnon, Jordan, Vaillancourt, Steane, & Potts, 2004; Neiman & Lively, 2004; Weston & Robertson, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the Southern Hemisphere (e.g. Tasmania, South Island of New Zealand), some species similarly appear to retreat from glaciated areas to refugial zones (Dussex, Wegmann, & Robertson, 2014; Kreger, Shaban, Wapstra, & Burridge, 2020; Leschen, Buckley, Harman, & Shulmeister, 2008; McCulloch et al., 2010; McKinnon, Jordan, Vaillancourt, Steane, & Potts, 2004; Neiman & Lively, 2004; Weston & Robertson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in North America, coastal and offshore microrefugia including Haida Gwaii (Pruett et al., 2013), Alexander Archipelago (Lucid & Cook, 2004), parts of the Arctic (Waltari & Cook, 2005) and even small pockets within the ice sheets (Marr, Allen, & Hebda, 2008), apparently facilitated species persistence outside major Beringian and Pacific Northwest refugia. In the Southern Hemisphere, microrefugia have been inferred to allow species persistence at sites affected by Pleistocene glaciations in Tasmania (Cliff, Wapstra, & Burridge, 2015; Kreger et al., 2020), Victoria (Bell, Griffin, Hoffmann, & Miller, 2018; Endo et al., 2015; Slatyer et al., 2014) and Patagonia (Breitman, Avila, Sites, & Morando, 2012), evidenced by high regional genetic diversity. In addition to idiosyncratic patterns generated by microrefugia, physiologically distinct lineages can exhibit divergent biogeographic histories under glaciation: temperate–adapted species typically undergo range contraction, whereas cold‐adapted, montane species experience range expansion via down‐slope extension of alpine habitat (DeChaine & Martin, 2004; Trewick, Wallis, & Morgan‐Richards, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…'flindersi' have suggested that the separation of drainages by tectonic shifts across the region (Dickinson et al, 2002; Gallagher et al, 2003) isolated populations following a dispersal event facilitated by river capture or flooding (Unmack et al, 2013). Regardless of the mechanism, divergence between Tasmanian and mainland lineages prior to the Pleistocene has been reported for birds (Lamb et al, 2019), lizards (Chapple et al, 2011; Dubey & Shine, 2010; Kreger et al, 2019), butterflies (Norgate et al, 2009) and other freshwater fish (Coleman et al, 2010), suggesting that climatic oscillations during the LGM alone did not drive the speciation of N . 'flindersi'.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the mechanism, divergence between Tasmanian and mainland lineages prior to the Pleistocene has been reported for birds (Lamb et al, 2019), lizards (Chapple et al, 2011;Dubey & Shine, 2010;Kreger et al, 2019), butterflies (Norgate et al, 2009 and other freshwater fish (Coleman et al, 2010), suggesting that climatic oscillations during the LGM alone did not drive the speciation of N.…”
Section: Eustatic Changes Drive Phylogeography and Speciation Along Coastal Habitatsmentioning
confidence: 99%